Antibacterial Evaluation of Lithium-Loaded Nanofibrous Poly(L-Lactic Acid) Membranes Fabricated via an Electrospinning Strategy - Liang, Chaoan; Jiang, Qiming; Yu, Yi; Xu, Tao; Sun, Hanyu; Deng, Feilong; Yu, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2021)
Lithium (Li) reportedly has anti-bacterial properties. Thus, it is an ideal option to modify barrier membranes used for guided bone regeneration to inhibit the bacterial adhesion. The aims of this study were to fabricate and characterize nanofibrous poly(L-lactic acid) (PLLA) membranes containing Li, and investigate their antibacterial effects on Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans in vitro. Li (5%Li, 10%Li, and 15%Li)-loaded nanofibrous PLLA membranes were fabricated using an electrospinning technique, and characterized via scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, a contact angle measuring device, and a universal testing machine. Sustained release of Li ions was measured over a 14-day period and biocompatibility of the Li-PLLA membranes was investigated. Evaluation of bacterial adhesion and antibacterial activity were conducted by bacterial colony counting, LIVE/DEAD staining and inhibition zone method using P.gingivalis and A.actinomycetemcomitans. Of the three Li-loaded membranes assessed, the 10%Li-PLLA membrane had the best mechanical properties and biocompatibility. Adhesion of both P.gingivalis and A.actinomycetemcomitans on Li-PLLA membranes was significantly lower than adhesion on pure PLLA membranes, particularly with regard to the 10%Li and 15%Li membranes. Significant antibacterial activity of Li-PLLA were also observed against according to the inhibition zone test. Given their better mechanical properties, biocompatibility, and antibacterial activity, PLLAs with 10%Li are a better choice for future clinical utilization. The pronounced antibacterial effects of Li-loaded PLLA membranes sets the stage for further application in guided bone regeneration.